PENGENALAN PENGENALAN MICROSOFT OFFICE DI TK DHARMA WANITA TUNGLUR BADAS KABUPATEN KEDIRI - Agus Sukoco Heru Sumarno; Eka Mandayatma; Imam Saukani; Donny Radianto; Agus Pracoyo; Gilang Al Azhar (Jurnal Pengabdian kepada Masyarakat, 2024)
Integrated Primary Education (TK Dharma Wanita) is a basic educational activity organized by and with the help of primary education officers. So, TK Dharma Wanita is a community initiative in the field of basic education, in which the village head is the responsible party. AA Gde Muninjaya (2002:169) states:“Basic education services are a form of integrated basic education services provided in primary education. Nowadays, computers are the tools used to process and create work reports, whether in the form of Word, Excel or PowerPoint data. Up to now, TK Dharma Wanita, headquartered in Sumberejo Badas Pare Village, Kediri Regency, still uses a conventional manual typewriter for reporting, which leads to many limitations that TK faces in terms of administrative operations. and data management.